The influence of learning motivation on high school students' mathematical creative thinking ability - Elis Rosmawati; Nia Kania; Iik Nurhikmayati (Universitas Sarjanawiyata Tamansiswa, 2023)
This research aims to investigate the impact of learning motivation on students' mathematical creativity. Employing correlational research techniques with a quantitative approach, the study focuses on the entire Class X population at MIPA Rajagaluh High School. The purposive sampling method was applied to select 30 students from Class X MIPA 6. Research tools included tests on creative thinking and surveys to gauge students' enthusiasm for learning. Data analysis involved correlation, linearity, and normalcy tests. The results revealed a noteworthy correlation between learning motivation and enhancing students' mathematical creative thinking skills. Learning motivation has a statistically significant influence on mathematical creative thinking abilities. These results underscore the importance of cultivating and sustaining students' learning motivation. It is recommended that teachers actively provide encouragement and guidance to nurture robust learning motivation among students.